2006
DOI: 10.1021/np0602970
|View full text |Cite
|
Sign up to set email alerts
|

Chaetocochins A−C, Epipolythiodioxopiperazines from Chaetomium cochliodes

Abstract: Three new epipolythiodioxopiperazines, chaetocochins A (1), B (2), and C (3), along with dethio-tetra (methylthio) chetomin (4) and chetomin (5), were isolated from the ethyl acetate extract of the solid-state fermented rice culture of the fungus Chaetomium cochliodes. Their structures were elucidated on the basis of spectroscopic analysis. Compounds 1, 3, and 4 exhibited significant cytotoxicity in vitro against cancer cell lines Bre-04, Lu-04, and N-04.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 10 publications
0
72
0
Order By: Relevance
“…The new saponins 1-4 were tested for their cytotoxic activities against five human cancer cell lines (HL-60, SMMC-7712, A-549, MCF-7, and SW480) in vitro. 8 and 20(R/S)-protopanaxtriol, 13 respectively, by comparison the spectroscopic and physical data with those previously reported values.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…The new saponins 1-4 were tested for their cytotoxic activities against five human cancer cell lines (HL-60, SMMC-7712, A-549, MCF-7, and SW480) in vitro. 8 and 20(R/S)-protopanaxtriol, 13 respectively, by comparison the spectroscopic and physical data with those previously reported values.…”
Section: Introductionmentioning
confidence: 53%
“…8 After steamed, a mass of low-pole triterpenoid saponins came forth. Being similar with the roots, the processed and the air-dried leaves must have different pharmacological activities and quality standard.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Briey, Chaetomium cochliodes (C.3.198) was isolated from soil collected from Sichuan Province, PR China and identied at the Institute of Microbiology, the Chinese Academy of Sciences (CAS). The seed culture medium was comprised of dextrose (20 g …”
Section: Fermentation Extraction and Isolation Of Chetominmentioning
confidence: 99%
“…Sporidesmins are a diverse class of natural products containing molecules with one or two epidithiodioxopiperazine (ETP) rings that display a wide variety of biological activities (Waksman & Bugie, 1944;Saito et al, 1988;Fujimoto et al, 2004;Gardiner et al, 2005;Li et al, 2006). While toxic to mammalian cells, studies have suggested that certain sporidesmins, namely bis-ETPs chetomin (Waksman & Bugie, 1944) and chaetocin (Hauser et al, 1970), may possess anticancer activity due to their ability to suppress neovascularization (Waksman & Bugie, 1944;Hauser et al, 1970;McInnes et al, 1976;Brewer et al, 1978;Kung et al, 2004).…”
Section: Commentmentioning
confidence: 99%